A single step analysis of plantar pressure distribution in tennis specific movements - Kornfeind, P.; Eckl, M.; Baca, A. (Journal of Human Sport & Exercise, 2019)
Studies indicate that injury risks in tennis depend on the playing surface type. In order to assess loading during tennis specific movements, plantar pressure parameters are determined and analyzed. So far, only comparisons between whole stride sequences on different surfaces have been performed showing some inconsistent results. We assumed that on the more slippery clay higher vertical forces are required to accelerate, and that on hard-court higher loadings occur during deceleration. Hence, we analyzed the influence of the playing surface on respective types of steps. Eight experienced male tennis players performed two different tennis specific movements on clay and hard-court. We used a Pedar-X insole measurement system for determining selected plantar pressure parameters for the whole foot as well as for the forefoot and rear foot area. Steps were categorized as accelerating or decelerating regarding the path of the center of pressure during impact of the foot on the ground. For accelerating steps, a multivariate analysis revealed significant differences (Pillai-Spur; p < .05) for both repeated factors as well as their interaction for both playing conditions. All loading parameters were significantly higher in the forefoot area on clay for one of the two playing conditions investigated. For decelerating steps, the multivariate analysis revealed significant differences for both repeated factors for one playing condition. Higher values were observed for all loading parameters in the rear foot area in both playing conditions on clay. Running styles during tennis specific movements depend on the court surface. Separate analyses of acceleration and deceleration steps may help revealing high-risk parts and periods.